Modular Type III Porous Liquids Based on Porous Organic Cage Microparticles. (18th September 2021) - Kai, Aiting; Egleston, Benjamin D.; Tarzia, Andrew; Clowes, Rob; Briggs, Michael E.; Jelfs, Kim E.; Cooper, Andrew I.; Greenaway, Rebecca L.
Abstract: The dispersion of particulate porous solids in size‐excluded liquids has emerged as a method to create Type III porous liquids, mostly using insoluble microporous materials such as metal–organic frameworks and zeolites. Here, the first examples of Type III porous liquids based on porous organic cages (POCs) are presented. By exploiting the solution processability of the POCs, racemic and quasiracemic cage microparticles are formed by chiral recognition. Dispersion of these porous microparticles in a range of size‐excluded liquids, including oils and ionic liquids, forms stable POC‐based Type III porous liquids. The flexible pairing between the solid POC particles and a carrier liquid allows the formation of a range of compositions, pore sizes, and other physicochemical properties to suit different applications and operating conditions. For example, it is shown that porous liquids with relatively low viscosities or high thermal stability can be produced. A 12.5 wt% Type III porous liquid comprising racemic POC microparticles and an ionic liquid, [BPy][NTf2 ], shows a CO2 working capacity (104.30 µmol gL −1 ) that is significantly higher than the neat ionic liquid (37.27 µmol gL −1 ) between 25 and 100 °C. This liquid is colloidally stable and can be recycled at least ten times without loss of CO2 capacity. Abstract : Porous liquids consisting of porous organic cage (POC) microparticles dispersed in size‐excluded oils and ionic liquids are formed. The flexible pairing between POC microparticles of different compositions and carrier liquid allows colloidally stable porous liquids to be produced with relatively low viscosities or high thermal stability. These systems exhibit enhanced CO2 and CH4 absorption, and can undergo pressure‐swing and temperature‐swing cycles.